Evaluation of the gallbladder and cystic duct patency with gadoxetate disodium enhanced MR cholangiography: prospective comparison of patients with normal gallbladder function and acute cholecystitis. (July 2015) - Yacoub, Joseph H; Yousuf, Ambereen; Agrawal, Garima; Thomas, Stephen; Appelbaum, Daniel E; Oto, Aytekin
Background: Using hepatocyte-specific magnetic resonance imaging (MRI) contrast agents such as gadoxetate disodium, MRI can provide functional information regarding the patency of the cystic duct similar to hepatobiliary scintigraphy in addition to anatomic images. Purpose: To describe the gadoxetate disodium enhanced MR cholangiography (GDE-MRC) findings in patients with acute cholecystitis and to compare them with findings in patients without acute cholecystitis and with normal hepatobiliary scintigraphy. Material and Methods: This study was HIPAA compliant and institutional review board approved. Twenty-three patients ( n  = 14 diagnosed with acute calculous cholecystitis based on ultrasound [US] or computed tomography [CT]; n  = 9 controls with normal hepatobiliary scintigraphy) were prospectively enrolled. All patients underwent GDE-MRC within 2 days of the US, CT, or hepatobiliary scintigraphy. GDE-MRC included axial gradient echo T1-weighted images before and 3, 10, 20, 30, and 60 min after injection of 10 mL of gadoxetate disodium. If excretion of contrast into the gallbladder was not noted at 60 min, intravenous morphine was administered (0.04 mg/kg) and images were acquired 30 min later. Results: In all nine controls, gadoxetate disodium was excreted into the gallbladder within 60 min (7/9 in <30 min). Twelve out of 14 patients with acute cholecystitis completed the study. Six out of 12 (50%) patients demonstrated contrast in their gallbladder within 1 h of administration similar to the control group (2/6 in <30 min). In the remaining 6/12 patients, contrast was not present in the gallbladder within 1 h from injection. Following morphine augmentation, contrast was subsequently noted in the gallbladder in 2/6 patients. Conclusion: GDE-MRC can assess the patency of the cystic duct. Delayed (>60 min) or lack of filling of the gallbladder during GDE-MRC supports the diagnosis of acute cholecystitis. However, filling of the gallbladder with contrast in <60 min does not exclude the diagnosis of acute calculous cholecystitis.